2020
DOI: 10.3390/ijerph17218254
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-Based Dispatching in an Emergency Medical Communication Centre: Sensitivity, Specificity, and the Area under the ROC Curve

Abstract: Background: Measuring the performance of emergency medical dispatch tools used in paramedic-staffed emergency medical communication centres (EMCCs) is rarely performed. The objectives of our study were, therefore, to measure the performance and accuracy of Geneva’s dispatch system based on symptom assessment, in particular, the performance of ambulance dispatching with lights and sirens (L&S) and to measure the effect of adding specific protocols for each symptom. Methods: We performed a prospective observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Comparing the rates of predictive values between and within dispatch systems requires knowledge about the prevalence of severity levels found in the field (i.e., detected by the reference standard) [ 33 ]. Therefore, it is important to note that the prevalence of the most urgent priorities (patients assessed as RETTS Red/Orange by the ambulance) was not entirely similar among the calls assessed by each group (45% for EMD and 33% for EMD supported by RN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the rates of predictive values between and within dispatch systems requires knowledge about the prevalence of severity levels found in the field (i.e., detected by the reference standard) [ 33 ]. Therefore, it is important to note that the prevalence of the most urgent priorities (patients assessed as RETTS Red/Orange by the ambulance) was not entirely similar among the calls assessed by each group (45% for EMD and 33% for EMD supported by RN).…”
Section: Discussionmentioning
confidence: 99%
“…International data on sensitivity for time-critical and severe calls has been reported to be as high as 93.3% and 86–87.5% for Australia and Switzerland respectively [ 33 35 ]. The sensitivity for cardiac arrest has been studied for different settings and reported to range from 65.9 to 86% in various countries [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that callers assessed their situation fairly well themselves, as only 5 (0.1%) serious situations (for 4464 assessments) were identified following a call to the COVID-19 medical helpline, compared with 735 (16.3%) serious situations (for 4493 assessments) on the 144 number ( Table 1 ). The provision of two telephone helplines (urgent or ambulance/non-urgent) therefore contributes to the performance of the EMCC triage, as the prevalence of severity is completely different depending on which line is called [ 24 ]. The skills available and the assessment tools used in EMCCs should be adapted to the condition of the patients assessed.…”
Section: Discussionmentioning
confidence: 99%
“…They handle all calls using a computer-aided dispatch system (ICAD ® from Hexagon AB ® ). For telephone assessments of patients, Geneva’s EMDs have used the symptom-based dispatch (SBD) system derived from the Swiss Emergency Triage Scale (SETS ® ) since 2013 [ 24 ]. Historically, there was not an Emergency Physician (EP) physically present in the EMCC, although EMDs had always had remote access to a physician in case of an assessment concern or medical question.…”
Section: Methodsmentioning
confidence: 99%
“…The data were also dichotomised into two groups according to EMS's criteria (Table 1)-one where the situation was considered urgent and the other where the situation was considered non-urgent. This allowed comparison with other studies that used the same dichotomisation [22][23][24]. The dichotomisation was made in a specific order in which the paramedic's assessment was primarily considered (Fig.…”
Section: Table 1 Criteria For the Priority Assessment Of The Emergenc...mentioning
confidence: 99%